Kualitas Fisik Dangke Susu Kerbau yang Ditambahakan Berbagai Level Pengumpalan Terong Duri - Wandira, Ica Ayu; Dohi, Muhammad; Sadia, I Nyoman (LPPM Universitas Mataram, 2025)
This study aimed to determine the effect of adding various levels of thorn eggplant (Solanum carolinense) as a coagulant on the physical properties of Sumbawa buffalo milk dangke. The materials used were Sumbawa buffalo milk and thorn eggplant. The study employed a completely randomized design (CRD) with 4 treatments and 4 replications: a control treatment (P0) with the addition of 1% papaya latex, P1 with 1% thorn eggplant, P2 with 2% thorn eggplant, and P3 with 3% thorn eggplant. The observed variables included acidity (pH), density, curd percentage, whey percentage, and lactic acid percentage of the dangke, analyzed using analysis of variance (ANOVA). The results indicated that the addition of thorn eggplant juice had a significant effect (P<0.05) on the curd percentage of Sumbawa buffalo milk dangke. However, it did not have a significant effect (P>0.05) on the acidity (pH), density, whey percentage, or lactic acid percentage. The best physical quality of buffalo milk dangke was achieved with the P2 treatment (2% thorn eggplant).